O ensino de eletrostática na educação básica baseado em experimentos históricos utilizando um kit de baixo custo - Oliveira, Ronaldo Furtado de (2019)
The present work was developed with the objective of making the teaching of electrostatics more attractive and meaningful for students of basic education. With the theoretical support of David Ausubel's Significant Learning, a series of experiments were carried out using a Kit, made by the students themselves, containing several historical experimental apparatus made with materials of easy access and low cost. With this kit the students explored several concepts in electrostatic, such as frictional, contact and inductive electrification, conductive and insulating materials, surface charge distribution, positive and negative charges, electrical grounding, electric potential, polarization of electric charges and electrostatic shielding. The research was carried out with students of the 3rd year of high school of a state school in the municipality of Vila Pavão ES. First, a questionnaire was given to the students, with the aim of probing their previous knowledge regarding the electrostatic content addressed in the research. In the course of the work, there was a great enthusiasm on the part of the students in constructing the experimental apparatus, with materials that are part of their daily life. They were very surprised and intrigued by the results obtained experimentally, this was very clear in their gestures and expressions. At the end of the research the students presented the experimental apparatus made by themselves a science fair organized by the college. Three months after the end of the work, the students wrote a free text telling the importance that the research had for them. In this text it can be observed that for all the students the construction of the experimental apparatuses, as well as the realization of the experiments, had a positive meaning for them. They all reported in their texts that it would be much easier to understand the contents of physics if they were worked experimentally and contextualized.